A European Roadmap for cycling - ECF proposal. - (:unkn) unknown (My University, 2015)
Cycling may not be a long-distance activity to the same extent as aviation, motorized transport and railways are, yet that does not mean that cycling has no link to EU (transport) policies, on the contrary. - The Single European Transport Area will remain inefficient as long as urban congestion and its impact on the first and last mile will not be properly addressed; - Road safety is a shared responsibility between Europe and Member States; - Cycling tourism is a growing business and should be adequately supported by the EU because since the Lisbon Treaty the EU has a role regarding tourism; - The transport sector will not meet its climate objective unless a modal shift in passenger transport takes place; the same applies to air quality and noise standards; - EU provides significant financial support (especially for the less developed member states) via ERDF, CEF and other Funds to develop transport infrastructure, urban and rural areas, SMEs. The EC should ensure that in case these funds are used for cycling related developments we will use its full potential. An EU Roadmap for Cycling is therefore a key instrument in raising the awareness for cycling on the political agenda. It has the unique potential to activate all relevant stakeholders, both at European and national level, to grow cycling.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrspolitik; Radverkehrsplanung; Radverkehrskonzept; Radverkehrsstrategie; Radverkehrspolitik